Case of colonization of the oral mucosa by Kodamaea ohmeri in a pediatric patient admitted to the icu of Darcy Vargas Children’s Hospital, São Paulo, Brazil - Teixeira Barbieri Ramos, Regina; Mendes Bonci, Mario; Volpe Arnoni, Mariana; Otsuka, Marcelo; de Souza Carvalho Melhem, Marcia; da Silva Ruiz, Luciana; Rodrigues Paula , Claudete (Revista de Patologia Tropical / Journal of Tropical Pathology, 2024)
Kodamaea ohmeri (Pichia ohmeri) is an emerging yeast that has caused different types of infections in humans, mainly in immunosuppressed and hospitalized patients. We report the case of a 3-year-old boy, admitted to the ICU, with colonization of the oral mucosa by K. ohmeri. The yeast strain collected from this patient’s oral mucosa was identified by the traditional method, Chromagar Candida, and studied by Maldi-Tof. Considering that the number of invasive cases caused by fungi has increased, mainly due to rare and emerging yeasts, their identification is extremely important for an accurate diagnosis and more effective treatment. KEY WORDS: Colonization; nosocomial infection; Kodamaea ohmeri.